A usina da discórdia : disputa pelo poder local - o caso das prisões em Constantina (1966) - Ferronatto, Caciana Luzia (2009)
This study aims to report on regional political disputes occurring within the Rio Grande do Sul, from the creation and development of municipal and corporate centers of hydroelectric power during the period 1959 to 1970. Thus, the object of analysis of this research is a dispute between two distinct political groups in Constantina city in Rio Grande do Sul, with a side effect the ideals of businessmen linked to the PSD, and other, professionals, affiliated to PTB. The facts, the reports, the context is guided by statements, official documents and also search for a theoretical foundation. During the study sought to understand two issues: first, the emancipation of Constantina in 1959, before the community united, divided into two distinct groups and rivals, seeking to clarify the causes of such disruption. The second reported on the arrests in 1966 not included in official documents for causes that they have occurred. Among the events is the Light and Power Plant Constantina Ltda. In the period between 1959 and 1970 unions were broken, incited disputes, arrests, humiliation - at times - in order to reach the desired development of a small inland region of Rio Grande do Sul, which today seeks sustainable development and appropriate to its inhabitants